THE EFFECT OF COMPANY SIZE, TAX AVOIDANCE, AND FINANCIAL DISTRESS ON PROFIT MANAGEMENT - Bella Puspita Sari; Mita Sicillia (Indonesian Journal Publisher, 2026)
This study aims to empirically prove the effect of firm size, tax avoidance, and financial distress on earnings management in property and real estate companies listed on the Indonesia Stock Exchange during the 2020-2024 period. This type of research is quantitative research using secondary methods. The number of research samples was determined by purposive sampling technique, resulting in a sample of 7 companies with a total of 92 observation data. The data used in this study were processed using E-views 12. The results of the study show that simultaneously company size, tax avoidance, and financial distress have an effect on earnings management with a value of (0.010715 <0.05), while partially firm size has no effect on earnings management with a value of (0.8853> 0.05), tax avoidance has an effect on earnings management (0.0052 <0.05) and financial distress has no effect on earnings management with a value of (0.2494> 0.05). The benefits of these findings can provide new insights for investors, regulators, and other stakeholders in assessing the quality of corporate financial reports and open up opportunities for further research on the dynamics of financial reports under various financial conditions of companies in Indonesia.